Behavioral Disorders in Preschool Children in Groups of Preschool Educational Institutions: Causes and Ways to Overcome Them - Valentуna Romenkova (Hryhorii Skovoroda University in Pereiaslav, 2024)
The article presents the results of empirical studies of children with negative behavior in a kindergarten group, studying the causes of behavior disorders and testing the effectiveness of methods for overcoming these violations. Various approaches have been used to shape socially acceptable behavior in children. The results of the study showed that a positive attitude towards others is primary in the development of social skills. Awareness of one's emotional state and verbalization of states, motives, and motivations for actions is possible after the child has formed a full-fledged emotional experience. Empirical data on the characteristics of the formation of a socially acceptable model of child behavior, including the experience of a positive attitude towards peers, are generalized. Experience in using social-emotional learning in a preschool education program, including learning to name emotions, states of others, etc. (cognitive component of socio-emotional development), shows the need to clarify the content and methods of working with preschool children.